Analysis Of Disclosure Of Criminal Acts Of Abuse Of Subsidized Fuel Based On Justice Values (Research Study At The Riau Islands Special Criminal Research Directorate) - Ade Kuncoro Ridwan; Fadlan, Fadlan; Eniyanti3, Eniyanti3 (UNES Law Review, 2024)
Misuse of transportation and commercial crimes are strictly regulated in Article 55 of Law Number 22 of 2001 concerning Oil and Natural Gas. Carrying out misuse without permission (illegal) has a specific aim and purpose to benefit oneself by exploiting or taking advantage of the conditions of a place or area that has a scarcity of fuel oil or is far from petrol stations.Methodologically, this research is a juridical empirical research with a legal and sociological approach. Finally, this research found that the enforcement of criminal law against commercial acts of subsidized fuel oil was found. As for the research results of the Special Criminal Investigation Directorate of the Riau Islands Regional Police, facts were found regarding the disclosure of 4 cases in 2022, 2 cases in 2023 and 2 cases in 2024, all of which advanced to the 2nd stage of delegation to the public prosecutor, the author assesses Law enforcement in theory, namely a form of effort carried out by law enforcement officials, which in the case above is the Police and aims to ensure whether existing and regulated laws are running as they should, and are in accordance with what is happening in the field. The efforts as intended consist of preventive and repressive efforts. Based on the results of research conducted by the author regarding the obstacles faced, namely internal controls including a) Limited Number of Personnel Number of personnel, b) Limited Operational Facilities; c) Personality or Mentality of Personnel in the practice of carrying out police duties and authority; d) Lack of Quality Personnel To create professional police; e) Limited Operational Funds To carry out their duties and roles as law enforcers, external obstacles include, a) Community factors b) lack of Legal Awareness; and finally the efforts made by the Special Criminal Investigation Directorate of the Riau Islands Regional Police a) Increasing community participation by conducting outreach; b) Placing Police personnel in distribution routes and vulnerable points; c) Conduct legal education to the community.